Neurohormonal Synchronization in the Face of Exhaustion: Unveiling the Cortisol-Oxytocin Crosstalk in Type 2 Diabetes Patients with Severe Distress and HPA Axis Blunting - Adang Muhammad Gugun; Yusuf Alam Romadhon; Suryanto; Alyssa Sindy Jatiningtyas; Sania Nurul Qurrata (Open Access Indonesian Journal of Medical Reviews, 2026)
Type 2 diabetes mellitus (T2DM) is increasingly conceptualized as a complex psychoneuroendocrine disorder. While acute physiological stress typically induces hypercortisolemia, chronic diabetes distress may lead to allostatic overload and Hypothalamic-Pituitary-Adrenal (HPA) axis blunting. The compensatory role of oxytocin, a stress-buffering neuropeptide, remains underexplored in this specific clinical phenotype. This study aimed to characterize the neuroendocrine phenotype of patients with uncontrolled T2DM and severe distress, specifically investigating the synchronization between serum cortisol and oxytocin as a marker of homeostatic regulation. In this analytic cross-sectional study, 86 patients with uncontrolled T2DM (HbA1c greater than or equal to 7.0%) and severe diabetes distress (Diabetes Distress Scale-17 mean score greater than or equal to 3.0) were recruited via purposive sampling. Strict exclusion criteria were applied for exogenous steroid use and renal failure to ensure biological validity. Fasting morning serum cortisol and oxytocin were analyzed using Enzyme-Linked Immunosorbent Assays (ELISA). Statistical analysis utilized Spearman’s rank correlation and multivariate linear regression, controlling for Body Mass Index and age. The cohort exhibited severe metabolic dysregulation (Mean HbA1c: 10.03 ± 2.10%) and psychological distress (Mean DDS: 4.65 ± 0.35). Paradoxically, mean morning cortisol was low-normal (170.32 ± 135.43 nmol/L), suggestive of HPA axis blunting rather than the expected hypercortisolemia. A robust positive correlation was observed between cortisol and oxytocin (r = 0.555, p < 0.001). Multivariate regression confirmed cortisol as a significant independent predictor of oxytocin levels (b = 0.521, p < 0.001), independent of metabolic confounders. In conclusion, patients with severe diabetes distress display a distinct phenotype of HPA axis exhaustion coupled with synchronized oxytocinergic activity. This suggests a preserved reactive mobilization mechanism where oxytocin is upregulated in tandem with adrenal output to buffer chronic allostatic load. These findings highlight the potential of the oxytocinergic system as a therapeutic target in diabetes burnout.